Plasma Metabolites Alert Patients With Chest Pain to Occurrence of Myocardial Infarction - Aa, Nan; Lu, Ying; Yu, Mengjie; Tang, Heng; Lu, Zhenyao; Sun, Runbing; Wang, Liansheng; Li, Chunjian; Yang, Zhijian; Aa, Jiye; Kong, Xiangqing; Wang, Guangji (Frontiers in Cardiovascular Medicine, 2021)
Myocardial infarction (MI) is fatal worldwide, the early warning of MI is life-saving. To expand our knowledge of MI, we analyzed plasma metabolites in MI and non-MI chest pain cases to identify risk markers for alerting about MI occurrence based on metabolomics. A total of 230 volunteers were recruited, including 146 inpatients with chest pain (85 MIs and 61 non-MI chest pain cases) and 84 control individuals. Gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry were applied to identify and quantify the plasma metabolites. Multivariate statistical analysis was utilized to analyze the data, and principal component analysis showed MI and non-MI cases had distinctly different metabolic patterns from the controls. MI could be clearly distinguished from non-MI chest pain cases in the scores plot of metabolomic data, even better than that based on the data constructed with medical history and clinical biochemical parameters. Pathway analysis highlighted an upregulated methionine metabolism and downregulated arginine biosynthesis in MI cases. Receiver operating characteristic curve (ROC) and adjusted odd ratio (OR) were calculated to evaluate potential markers for diagnosis and prediction ability of MI. Finally, gene expression profiles from GEO database were briefly discussed to study differential metabolites’ connection with plasma transcriptomics. Deoxyuridine(dU), homoserine and methionine scored highly in ROC (>0.91), sensitivity (>80%) and specificity (>94%), and they were correlated to LDH and AST (p<0.05). OR values suggested, after adjusting by lipid levels, age, smoking, diabetes and hypertension, that both high level of dU of positive log(OR)=3.01, methionine of log(OR)=3.48, and homoserine of log(OR)=1.61, and low level of isopentenyl diphosphate (IDP) of negative log(OR)=5.15, uracil of log(OR)= 2.38 and arginine of log(OR)= 0.82, were risk factors of MI. For the first time, our data suggested metabolites involved in pyrimidine and arginine metabolisms, such as dU, homoserine, IDP, uracil, together with methionine and arginine, are candidate risk markers to alert an occurrence of MI among patients with cardiac-chest pains, and they are potential markers for MI diagnosis and prediction of MI occurrence.